Experiences and Perceptions of Diabetes Patients and Families in Implementing Diabetic Self-Care: A Qualitative Study - Diani, Noor; Nurachmah, Elly; Dahlia, Debi; Martha, Evi; Setyowati, Setyowati; Nafi’ah, Rizka Hayyu; Noor, M. Fakhruddin (Jurnal Keperawatan Soedirman, 2025)
Diabetic patients experience various challenges in adhering to self-care practices, such as glucose monitoring, diet management, and physical activity, that require a continuum of care. The study aimed to explore the experiences and perceptions of diabetic patients regarding self-care and the factors that influence their adherence. The study used a qualitative method with a phenomenological approach, involving five participants from South Kalimantan. Data were collected through semi-structured in-depth interviews and analysed using the Colaizzi method to identify key themes reflecting self-care experiences. The study results showed that the five participants' understanding of self-care was still diverse, especially regarding glucose monitoring and physical activity. Family support was a significant factor in improving self-care adherence, although the family's understanding of diabetes management sometimes hindered these efforts. Other barriers included limited healthcare access, high-cost medication, and monitoring devices. In addition, participants showed optimism towards future health, but were concerned about the sustainability of self-care practices in the long term. The importance of diabetes management programmes that involve education for patients and families, and policies that support more affordable access to healthcare. A comprehensive approach to diabetes management, including family and community support, can improve patient adherence to self-care and quality of life.